Enhancing twelve grader’s proficiency in performing procedure text using flashcards - Sulistyowati, Ana Dwi; Indah, Rohmani Nur; Syaifulloh, Burhanudin (Universitas Riau Kepulauan, 2023)
Performing procedure text in English has its own complexities especially for twelve graders since they need to clearly present a series of action in logical order. When students performed their presentations online, they felt it was not as difficult as having an onsite presentation. Yet, the transition of learning mode in the current post-pandemic brings a greater challenge to them. To overcome this issue, this classroom action research offered the use of flashcards containing images and keywords that became the main attraction for students. The participants of this study were 28 students of a senior high school in Kediri. The results indicate that flashcards were significantly helpful in enhancing the twelve graders proficiency in performing procedure text with the increase from pre-test score of 76.79 into the post-test score 83.79 with a significance level of 000. It means that flashcards are able to improve student learning outcomes, especially in performing speaking for procedure text. Therefore, English speaking teachers are recommended to use flashcard to enrich student’s vocabulary and support the systematic presentation of procedure text.